TEACHERS' PERCEPTIONS ON THE QUALITY OF CLASS X SMA BIOLOGY BSE BOOKS - Badrud Tamam (Yayasan Citra Dharma Cindekia, 2021)
This study aimed to determine the teacher's perception of the quality of class X BSE Biology books used in high school. This research was conducted from March to April 2016 at public high schools in Malang City. The sample used was ten teachers who taught at class X high school. The instrument was a questionnaire with 67 items divided into four indicators for making textbooks: content feasibility, language, presentation, and graphics. The instrument used also used semi-structured interviews consisting of 6 question items. Data analysis used descriptive analysis. Based on the study results, it is known that the BSE Biology book for class X on the content feasibility component the teacher perceives quite well with a score of 2.70. The teacher's perception regarding the language component is quite good, with a score of 2.81, and the teacher's perception of the presentation component is quite good, with a score of 2.90. It is the highest score from the teacher's perception, and the graphic component is the lowest, equal to 2.50, with a fairly good perception category.